The impact of game models and learning motivation on manipulative movement skills in elementary school students - Dewi, Rahma; Akhmad, Imran; Pane, Bessy Sitorus; Verawati, Indah; Destya, Muhammad Reza (Edelweiss Applied Science and Technology, 2025)
This study examines the impact of two distinct game models and students' learning motivation on the acquisition of fundamental manipulative movement skills in primary school students. The study employed a 2×2 factorial experimental design at Gajah Mada Elementary School in Medan City, involving 40 students who were evenly divided into two groups according to game type (individual vs. group) and motivation level (high vs. low). The researchers used a two-way ANOVA at a 5% significance level to analyze the data obtained from skill testing. The Lilliefors test was used to assess normality in the data, while the F-test and Bartlett's test were employed to evaluate homogeneity of variance. The results showed that the game model had a significant effect on manipulative movement skills (Fcount = 5.87 > Ftable = 4.085), with group games performing better. Learning motivation also had a significant effect on skill acquisition (Fcount = 75.7 > Ftable = 4.085). There was also a substantial interaction between the game model and motivation (Fcount = 32.6 > Ftable = 4.085), indicating that the effectiveness of a game model relies on the student's motivation. These findings suggest that integrating suitable game models with targeted tactics to promote motivation could significantly enhance students' fundamental motor skills in physical education.